Obstetric outcomes in women with rheumatic disease and COVID-19 in the context of vaccination status. (19th September 2022) - Maguire, Sinead; Al-Emadi, Samar; Alba, Paula; Aguiar, Mathia Cecilia; Al Lawati, Talal; Alle, Gelsomina; Bermas, Bonnie; Bhana, Suleman; Branimir, Anic; Bulina, Inita; Clowse, Megan; Cogo, Karina; et al.
Abstract: Objective: To describe obstetric outcomes based on COVID-19 vaccination status, in women with rheumatic and musculoskeletal diseases (RMDs) who developed COVID-19 during pregnancy. Methods: Data regarding pregnant women entered into the COVID-19 Global Rheumatology Alliance registry from 24 March 2020–25 February 2022 were analysed. Obstetric outcomes were stratified by number of COVID-19 vaccine doses received prior to COVID-19 infection in pregnancy. Descriptive differences between groups were tested using the chi-squared or Fisher's exact test. Results: There were 73 pregnancies in 73 women with RMD and COVID-19. Overall, 24.7% (18) of pregnancies were ongoing, while of the 55 completed pregnancies, 90.9% (50) of pregnancies resulted in livebirths. At the time of COVID-19 diagnosis, 60.3% ( n  = 44) of women were unvaccinated, 4.1% ( n  = 3) had received one vaccine dose while 35.6% ( n  = 26) had two or more doses. Although 83.6% ( n  = 61) of women required no treatment for COVID-19, 20.5% ( n  = 15) required hospital admission. COVID-19 resulted in delivery in 6.8% ( n  = 3) of unvaccinated women and 3.8% ( n  = 1) of fully vaccinated women. There was a greater number of preterm births (PTB) in unvaccinated women compared with fully vaccinated 29.5% ( n  = 13) vs 18.2% ( n  = 2). Conclusions: In this descriptive study, unvaccinated pregnant women with RMD and COVID-19 had a greater number of PTB compared with those fully vaccinated against COVID-19. Additionally, the need for COVID-19 pharmacological treatment was uncommon in pregnant women with RMD regardless of vaccination status. These results support active promotion of COVID-19 vaccination in women with RMD who are pregnant or planning a pregnancy. Video Abstract: